Half of Postoperative Deaths After Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy Could be Preventable: A French Root Cause Analysis on 5562 Patients. Issue 5 (29th November 2021) - Houlzé-Laroye, Constance; Glehen, Olivier; Sgarbura, Olivia; Gayat, Etienne; Sourrouille, Isabelle; Tuech, Jean-Jacques; Delhorme, Jean-Baptiste; Dumont, Frédéric; Ceribelli, Cécilia; Amroun, Koceila; Arvieux, Catherine; Moszkowicz, David; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To perform a retrospective root-cause analysis of postoperative death after CRS and HIPEC procedures. Background: The combination of CRS and HIPEC is an effective therapeutic strategy to treat peritoneal surface malignancies, however it is associated with significant postoperative mortality. Methods: All patients treated with a combination of CRS and HIPEC between January 2009 and December 2018 in 22 French centers and died in the hospital, were retrospectively analyzed. Perioperative data of the 101 patients were collected by a local senior surgeon with a sole junior surgeon. Three independent experts investigated the typical root cause of death and provided conclusions on whether postoperative death was preventable (PREV group) or not (NON-PREV group). A typical root cause of preventable postoperative death was classified on a cause-and-effect diagram. Results: Of the 5562 CRS+HIPEC procedures performed, 101 in-hospital deaths (1.8%) were identified, of which a total of 18 patients of 70 years old and above and 20 patients with ASA score of 3. Etiology of peritoneal disease was mainly colorectal. A total of 54 patients (53%) were classified in the PREV group and 47 patients (47%) in the NON-PREV group. The results of the study show that in the PREV group, WHO performance status 1-2 was more frequent and the Median Peritoneal Cancer Index was higher compared with those of the NON-PREV group. The cause of death in the PREV group was classified as: (i) preoperatively for debatable indication (59%), (ii) intraoperatively (30%) and (iii) postoperatively in 17 patients (31%). A multifactorial cause of death was found in 11 patients (20%). Conclusion: More than half of the postoperative deaths after combined CRS and HIPEC may be preventable, mainly by following guidelines regarding preoperative selection of the patients and adequate intraoperative decisions.